Health and democratization as contradictory policy goals: sport in Zaragoza city. Issue 10 (14th September 2020) - Marcen, Celia; Malcolm, Dominic
Abstract: This paper examines the incompatibility of health and democratization policy goals in the promotion of sport and physical activity. Empirically the paper is based on a comparison of two population surveys (2009 and 2015) of behaviours and attitudes within a single city. Theoretically the paper extends previous explanations that have attributed changes in sports participation to differentiation and individualization by drawing on the works of Elias and Bourdieu in relation to social classes and embodied behaviour. The data reveal the changing social structure of participation, the relative popularity of different types of sport and peoples' attitudes towards being physically active. Specifically, the paper demonstrates that while sports participation has increased overall, the participation patterns of different social groups have become increasingly differentiated. It further argues that while the increase in health-oriented sports participation is partly driven by citizens' desires to self-regulate the body, the goals of democratizing sports participation are less likely to be achieved. In conclusion we suggest that while sports participation aligns closely with broader trends towards bodily and health self-management, health has concomitantly become an increasingly important marker of social stratification which thus counteracts the movement towards the democratization of sports participation.